Changes in body fluids during endurance rowing training - Jurimae, J.; Jurimae, T.; Pihl, E. (Annales of the New York Academy of Sciences, 2000)
The aim of this study was to investigate the influence of long-lasting, extensive rowing training on body fluids in 12 experienced rowers (23.3 +/- 6.3 years, 188.7 +/- 5.9 cm, 82.0 +/- 10.8 kg, body mass index [BMI] 23.7 +/- 2.1). All rowers had a light traditional breakfast about 3 h before the training. The subjects rowed 2 h 17 min and covered 22.6 +/- 2.5 km. Before and immediately after the training session and after 30, 60, and 120 min of recovery, body fluid balance was measured using a multiple-frequency impedance device (Multiscan 5000, Bodystat Ltd., UK). Body resistance was measured at the right side of the body. Extracellular (ECW), intracellular (ICW), and total (TBW) body water were measured at 5, 200, and 50 kHz, respectively. Blood hemoglobin (Hgb) and hemotocrit (Hct) were measured, and changes in blood volume (BV), plasma volume (PV), and cell volume (CV) were measured according to Dill and Costill (1974). The body weight of the rowers decreased significantly (p < 0.05) from 82.0 +/- 10.8 kg to 80.6 +/- 11.2 kg during the endurance training. There were no significant changes in TBW immediately after the training session. Significant changes in the content of TBW occurred during the first 30 min of recovery (48.7 +/- 4.4 to 47.9 +/- 4.1; p < 0.05). The amount of ECW also decreased significantly during the first 30 min of recovery (23.3 +/- 2.0 to 22.7 +/- 1.91; p < 0.05). There were no significant changes in the balance of ECW. BV decreased during the training session by 2.5 +/- 5.2% (p < 0.05). There were significant relationships (p < 0.05) between the covered distance and the following parameters after the training session: body weight (r = -0.75), TBW (r = -0.75), and ECW (r = -0.83). Changes in the blood parameters did not correlate significantly with changes in body fluids and training volume. It was concluded that extensive rowing training significantly changed the balance of body fluids in rowers. Ann N Y Acad Sci 2000 May;904:353-8